Malaysian Perspectives on Managing Financial Crisis - Zhang, Teresa Qiao Wen (2009)
Motivated by a fascination with the question of how financial crisis can be avoided or controlled, this study explores the perspectives of the Malaysian financial community on the 1997-1998 Asian regional financial crisis and the 2007-2009 global financial crisis. Answers have been sought to questions on the assessment of the quality of the 1997 Malaysian crisis response, the degree of learning from that crisis and the subsequent reforms that were implemented. Answers to questions about the Malaysian financial community’s view of the current crisis, Malaysia’s resilience to it and the extent to which the international lessons from it are of relevance to the country were also sought. The use was made of four data sets. The first two were a questionnaire survey of and a series of semi-structured interviews with members of the Malaysian financial community and those with an interest in financial crisis, including politicians, journalists and crisis specialists. The next data set was derived from official macroeconomic and other statistics from the central bank and relevant ministries. The fourth data set was the academic and grey literature produced by Malaysians on the topic of financial crisis. These four provided a degree of triangulation, to add depth to the analysis. The study concluded that, according to the Malaysia financial community, the country generally handled the 1997 crisis well and subsequently implemented reforms that demonstrated significant learning from the crisis. In the view of the of the Malaysian financial community consulted, this seems to have strengthened Malaysia’s resilience against further financial crisis. This was demonstrated by the relatively unscathed manner in which the banking sector emerged from the 2007-2009 crisis. Opinion was divided over whether this crisis, perceived to have been different from 1997, had lessons that were of relevance to Malaysia. The three implications for practice were that continuous learning is needed to improve crisis resilience, that concepts from strategic crisis management theory should be used to supplement the technical responses to financial crisis, and that prescriptions from international financial institutions and mainstream economists should be viewed sceptically and that the unconventional and counter-intuitive solution should always be considered. Despite its limitations, this study has identified the probable emergence of an Asian form of capitalism that merits further research.